Awareness and perceptions of school children about female feticide in urban Ludhiana - Chaudhary Anurag; Satija Mahesh; Sharma Sarit; Singh GPI; Soni R; Sachar R (Wolters Kluwer Medknow Publications, 2010)
Background: Although the Indian girl child′s position is precarious throughout the country, she remains the most vulnerable in Punjab. Objectives: To assess the awareness and perceptions of school children regarding female feticide. Study Design: Cross- sectional study. Materials and Methods: The study involved collection of information regarding knowledge and perception of school students about female feticide using multiple choice questionnaire. A total of 527 students between the age group of 11-18 years of various schools of district Ludhiana, Punjab were the study subjects. They had come to participate in the poster competition on organ donation (SAARC Transplant games), organized by Department of Community Medicine, D.M.C and H, Ludhiana. Results: Out of total 527 students, 97.9% were aware of female feticide. Main source of information was TV (56%), followed by newspaper (33%). Majority of the students (65.2 %) felt that discrimination between boys and girls is prevalent in the society. Regarding perception of school students for curbing this social evil, 37.8% school students were of the view that awareness among the masses is the solution to stop this practice, while 25% of the students responded that equal status to girls will stop this practice of female feticide. Conclusions: The school students had optimum level of awareness about female feticide and almost all of them strongly felt that this harmful practice should be stopped altogether.